EFEKTIVITAS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DI SD NO. 10 PEDUNGAN, DENPASAR - Chindytia; Anak Agung Gede Agung; Anak Agung Ayu Ratih Erawati; Ni Kadek Mita Prasetia; Okta Monica Putri, Ni Kadek Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of School-Based Management (SBM) implementation at SD No. 10 Pedungan, South Denpasar, Bali. A qualitative descriptive case study method was employed, complemented by SWOT analysis as a strategic evaluation instrument. The results indicate that SBM has been effectively implemented in curriculum management, financial management, and community relations, as evidenced by the school’s Grade A accreditation. Key success factors include the principal’s transformational leadership, a collaborative culture rooted in Tri Hita Karana values, and an active school committee. Main obstacles include the absence of an integrated Management Information System (MIS), gaps in teachers’ digital competency, and limited development budget. SWOT analysis recommends SO and WO strategies as priorities for optimizing synergy between internal strengths and external opportunities.